Oculoplastic Surgery Atlas Eyelid and Lacrimal Disorders (Springer International Publishing, 2018)
When the first edition of this atlas was published in 2002, it was well received throughout the oculoplastic and ophthalmology community for its simplicity and clinical focus. Now, a decade later, surgical techniques have been updated to reflect current practice models and advances in technology. The field of oculoplastic surgery has grown and evolved to include all aspects of eyelid and facial plastic surgery and the literature must now reflect the advancements of this field. Oculoplastic Surgery Atlas: Eyelid and Lacrimal Disorders, 2nd edition combines text and diagrams, plus surgical videos that enable readers to perform this surgery with the best possible instruction and preparation. Written for ophthalmology specialists and residents, this new edition presents many aspects of facial cosmetic surgery, including lacrimal anatomy, nasolacrimal duct disorders, canaliculitis, and canalicular involving eyelid laceration. Reviews of the previous edition: " It is the work of the well-known Detroit oculoplastic group ... . When one reads through this book ... there really is nothing else that is needed in terms of teaching of oculoplastic surgery. ... This is a book which I would strongly recommend to those engaged in this specialty ... . I highly recommend it to all trainees and to those who feel that their knowledge may be a little rusty ... ." (I. T. Jackson, European Journal of Plastic Surgery, Vol. 26 (8), 2004) "The book is intended for ophthalmologists, otolaryngologists, plastic and general surgeons who want a better understanding of eyelid surgery. It succeeds in providing a practical guide for the practitioner ... . The standard of the content is on the whole high. The surprise bonuses are the two compact discs inside the back cover. Here the reader/viewer is treated to a high-quality, well-edited digital video of oculoplastic surgery. ... This is the first multi-media surgical atlas I have seen and it represents a valuable educational tool." (Susan Hague, Eye News, Vol. 9 (3), 2002).